(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
: Supracondylar humeral fracture is the second most common pediatric fracture, occur most frequently in child aged (5 – 7) years, and more common in boys than girls. Due to specific anatomical considerations the supracondylar region is at high risk for fracture. This study was undertaken to evaluate the outcome of different types of management according to the severity of the fracture.Materials and methods: This is a prospective case series study, carried out in Sulaymaniyah at Emergency and Shar hospitals. 28 cases were studied between August 2018 to January 2019 including follow up over three months. All patients were treated operatively and conservatively according to the fracture severity. Follow up was done by using Flynn’s criteria (cosmetic and functional factors) and the fracture union tested clinically and by X-ray.Results: Out of 32 cases, 28 were complete the follow up period and included in this study. Age range from (2 – 13) years with (Mean ± SD = 6.4 ± 3.1). The most common frequent fracture type was Gartland type III (42.8%). The outcome according to Flynn’s criteria, cosmetically 20 (71.4%) have excellent outcome and 8 (28.6%) have good outcome. Were for function, 15 (53.6%) have excellent outcome, 10 (35.7%) have good outcome and 3 (10.7%) have fair outcome